Fault diagnosis of a squirrel cage induction motor fed by an inverter using lissajous curve of an auxiliary winding voltage - Yakout Khadouj Jelbaoui; El Menzhi Lamiaà; Abdallah Saad (Institute of Advanced Engineering and Science, 2021)
The development of electronic power components has allowed the increase of the induction machine performance. Indeed, monitoring squirrel cage induction motors driven through rectifiers and inverters has been a major concern. This paper presents a new method to diagnose the combination inverter-machine faults. This technic considers an auxiliary winding which is a small coil inserted between two stator phases. It is based on Lissajous curve of this auxiliary winding voltage Park components. For this purpose, modeling the electromechanical conversion chain is necessary. The focus will particularly be on modeling both the squirrel cage induction machine and the inverter in a non-defected case which is a reference. Moreover, the explicit expressions developed for the inserted winding voltage and its Park components will be presented. The simulation results show the effectiveness of the proposed method.